ANALISA HUKUM ATAS PERBEDAAN BENTUK KETERANGAN WARIS YANG DIBUAT DALAM PRAKTEK NOTARIS DI KOTA MEDAN - OKRI JUNANDA YURIZ (PREMISE LAW JURNAL, 2016)
Making an inheritance certificate for a Chinese Indonesian citizen is regulated under Article 111, paragraph 1, letter c of PMNA No. 3/1997 which states that inheritance certificate for a Chinese Indonesian citizen is drawn up by a Notary. In practice, a Notary draws up inheritance certificate in three different types: authentic deed, in originali deed, and underhanded deed. In its authentic form, it is called Inheritance Certificate, in its underhanded and in originali form it is called Inheritance Rights. The problems of the research were as follows: how about the difference in the forms of inheritance certificates made by Notaries in Medan, how about the legal consequence of the different forms of inheritance certificate, and how about the advantage and the disadvantage of making different forms of   inheritance certificate. Keywords            :               Notarial Deed, Inheritance Certificate, Authentic Deed, Underhanded Deed, In Originali Deed